Smart Laundry System - Qing, Tan Yi; Omar, Mohd. Nizam (Multidisciplinary Applied Research and Innovation, 2023)
With the continuous progress and innovation of science and technology, a human can manipulate everything with a smartphone. Continuous innovation of mobile applications and system brings a lot of convenience to mankind. However, the smart laundry system mobile application is not developed as other kinds of mobile applications. Furthermore, there is still exist of laundry management using manual way, which required constant checking by staff. Customers also faced many problems in using laundry services such as wasting a lot of time using laundry services, and limited way of payment methods. Hence, this study aims to solve the problems by designing and developing a mobile application that can provide a platform for customer and laundry owner to trade on and a system that allow laundry owner to manage their laundry efficiently. The methodology in the development of the One Source Smart Laundry System is the Rapid Application Development (RAD) Methodology. By using this methodology, a prototype of the One Source Smart Laundry System is being developed based on the requirements gathered. Then, the final prototype is evaluated by 32 respondents in terms of design, content, functionality, and usability. From the evaluation result, the respondents are satisfied with the One Source Smart Laundry System mobile application. This study contributes toward an understanding of the system requirements and user interface of a mobile application that can provide a platform for customer and laundry owner to trade on and a system that allow laundry owner to manage their laundry efficiently.